Peran Aktor Lokal dalam Implementasi Program Pengelolaan Sampah Berbasis Masyarakat di Kampung Jambangan Surabaya - Sukmawati, Ananda Nur Vadila; Khasanah, Afidah Lailatul; Wahyudi, Kalvin Edo (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
This study aims to examine the role of local actors in implementing a community-based waste management program in Kampung Jambangan, Surabaya, and analyze the influence of their involvement on the program's success. The method used is descriptive qualitative research to obtain a comprehensive picture of the program's implementation in the field. Research data were collected through interviews with relevant informants, observations of waste management activities, and review of various relevant documents. Furthermore, the data were analyzed using interactive analysis techniques referring to the concepts of Miles and Huberman. The results show that the program's success is supported by the synergy of various parties, such as the local government, environmental cadres, RT/RW administrators, and the local community. Each party plays a different but mutually supportive role, starting from policy formulation, community empowerment, activity coordination, and the implementation of waste management in daily life. In addition, smooth communication, resource availability, and active community participation are important elements that contribute to the sustainability of the community-based waste management program in Kampung Jambangan.Keyword :  ommunity-based waste management, local actors, community participation, community empowerment, Kampung Jambangan